MANAJEMEN MUTU TERPADU DI SMK NEGERI 7 SAMARINDA - Hasbi Sjamsir; Muhammad Amir M; Muhammad Yusuf (Manajemen Pendidikan Program Doktor, 2021)
To face of an increasingly strong and competitive Globalization Era, implementing MMT at schools is very important for the long-term success of school organizations and is a source of excellence in order to create performance and productivity towards achieving continuous Quality Management. The purpose of this study was to determine: (1) the application of MMT at Samarinda State Vocational High School in an effort to improve school quality management, (2) the level of achievement of Integrated Quality Management (MMT) at Samarinda State Vocational School in an effort to improve school quality management, (3) which was an obstacle to Integrated Quality Management (MMT) at Samarinda State Vocational High School in an effort to improve school quality management. This study uses a qualitative descriptive design. The interview guide is used to explore information about the application, level of achievement and factors that become obstacles to Integrated Quality Management (MMT) at SMK Negeri 7 Samarinda. The results showed that: (1) the application of MMT to Samarinda State Vocational High School seven had been implemented and went well, (2) the level of achievement of MMT at Vocational High School seven had shown good results with increasing students, increasing educator HR, good quality of facilities and infrastructure, as well as a conducive work and learning environment, (3) Factors that become obstacles to the application of MMT to Vocational High School seven are the use of technology that is not maximized for some teachers, there are still some internal parties lacking commitment in quality assurance, learning methods, and lack of discipline of teachers in teaching. It can be concluded that the results of the research on the implementation of MMT in Samarinda State Vocational High School 7 Kalimantan through the implementation of MMT found an increase in performance and school quality assurance.